Sexual pain disorder with anxiety and depressive psychopathology as complication: a case-report - Ameerah Adeelah MA,; Kanit TD,; Hatta Sidi, (Fakulti Perubatan, UKM, 2016)
Vaginismus is a sexual dysfunction which results from vaginal musculature spasm and makes the penetration almost impossible. It is commonly associated with significant emotional distress. On several occasions, fear of pain during sexual intercourse may perpetuate the sexual dysfunction. We report a case of primary vaginismus that was associated with psychiatric squeale of anxiety and depression psychopathology. It suggests that psychological problems related to a mental-health problem in vaginismus should be dealt adequately for a holistic approach. A combination of behavioural, psychological and pharmacological treatment is important to ensure a good prognosis outcome.